2019
DOI: 10.1080/10826068.2018.1536988
|View full text |Cite
|
Sign up to set email alerts
|

A fast and simple approach to optimize the unit operation high pressure homogenization - a case study for a soluble therapeutic protein inE. coli

Abstract: View related articles View Crossmark data Citing articles: 2 View citing articles A fast and simple approach to optimize the unit operation high pressure homogenization-a case study for a soluble therapeutic protein in E. coli

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Primary recovery in E. coli processes usually requires cell disruption by high‐pressure homogenization to make the product available for purification. Homogenization is a critical unit operation that may have a large impact on further downstream steps, for example by introducing variance in pH or product concentration, and therefore requires optimization 23–25 . The major advantage of extracellular protein production is that primary recovery is simplified by omitting this cell disruption step.…”
Section: Resultsmentioning
confidence: 99%
“…Primary recovery in E. coli processes usually requires cell disruption by high‐pressure homogenization to make the product available for purification. Homogenization is a critical unit operation that may have a large impact on further downstream steps, for example by introducing variance in pH or product concentration, and therefore requires optimization 23–25 . The major advantage of extracellular protein production is that primary recovery is simplified by omitting this cell disruption step.…”
Section: Resultsmentioning
confidence: 99%
“…The use of DoE has also been established to increase the performance of downstream process development. In one study, high-pressure homogenization was used to screen critical process parameters (CPPs) using DoE to enhance product titer and achieve adequate product quality, based on predefined critical quality attributes (CQAs) (Pekarsky et al, 2019). A process for the purification of scFv using mixed-mode chromatography was developed using DoE, and it was found that the optimized conditions enabled binding of the scFv to Capto Adhere TM below its theoretical pI, with the majority of HCPs in the flow-through (Sakhnini et al, 2019).…”
Section: Design Of Experiments (Doe) Approachmentioning
confidence: 99%
“…Many studies also analyze process and product specific nuances, exploring avenues for improved efficiency, quality, and control. These include investigating the interplay between upstream and downstream unit operations on inclusion body quality and yield (Eggenreich et al, 2020;Slouka et al, 2018), characterizing the impact of processinduced chemical modifications to monoclonal antibodies (Hutterer et al, 2013), improved cell disruption process monitoring strategies (Eggenreich et al, 2017), and strategies for process optimization (Dopp and Reuel, 2018;Metzger et al, 2020;Pekarsky et al, 2019).…”
Section: Biopharmaceutical and Biotechnology Applicationsmentioning
confidence: 99%